Cultural Psychology - Muhyiddin Shakoor (International Institute of Islamic Thought, 1998)
For the past thirty years, Michael Cole has been a prolific writer, researcher, and creative thinker in the field of developmental psychology. In Cultural Psychology: A Once and Future Discipline, he attempts to synthesize what he has learned and to set forth an approach to developmental psychology from an historical and culrural perspective. Hence, a culturally sensitive science of human development appears to be Cole's objective. He describes cultural psychology as "the study of culture's role in the mental life of human beings." His subtitle suggests that culrural psychology was a discipline which existed in former times and will exist again in the future. Cole argues in favor of what is known as a "second psychology," which moves beyond the confines of traditional and contemporary psychological thinking about how the human mind is understood. The former psychology, described as naturalistic, has focused on the familiar and more classical views. Such views evolved from our analysis of mental phenomena developed from ideas, sensations, reflexes, and experiences with sensorimotor connections. Alternately, the latter approach, "second psychology," looks at the higher mental processes formed by cultures. These include things such as languages, myths, and social practices within the individual's social context. The author reviews the evolution of thought through several contemporary thinkers who, in his view, have contributed the substance of a scientific, second psychology-oriented methodology necessary for a viable, efficacious culrural psychology. That is to say a psychology which is sensitive to social and culrural contexts. The context includes such things as language, riruals, and routines as they contribute to understanding people in terms of their interdependence, cooperation, and essential humanity ...